AGGRESSION AS A MEANS OF DEFENSE - Tuychiyevna, Razikova Lola; Aliya, Хulaeva (PT. Antis International Publisher, 2025)
Objective: The objective of this study is to explore aggression as a psychological defense mechanism utilized by individuals to shield themselves from external threats or internal conflicts. It aims to analyze the complexity of aggression and its dual consequences, both positive and negative. Methods: The article employs a psychological approach to understand aggression, focusing on its triggers and manifestations. It examines both external stimuli and internal psychological states, such as stress, anxiety, and fear, as potential causes of aggressive behavior. Results: The findings indicate that aggression is a multifaceted process that operates beyond immediate external triggers. Internal psychological states play a significant role in shaping aggressive responses. This highlights the importance of considering both environmental and psychological factors in understanding aggression. Novelty: The study provides a nuanced perspective by emphasizing that aggression is not solely a reaction to external stimuli but also a defense mechanism influenced by internal psychological conditions. This dual focus on external and internal triggers offers a broader understanding of the complexities of aggression.